Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1051/0004-6361:20079275
|View full text |Cite
|
Sign up to set email alerts
|

A mini-survey of ultracool dwarfs at 4.9 GHz

Abstract: Context. A selection of ultracool dwarfs are known to be radio active, with both gyrosynchrotron emission and the electron cyclotron maser instability being given as likely emission mechanisms. Aims. We explore whether ultracool dwarfs previously undetected at 8.5 GHz may be detectable at a lower frequency. Methods. We select a sample of fast rotating ultracool dwarfs with no detectable radio activity at 8.5 GHz, observing each of them at 4.9 GHz. Results. From the 8 dwarfs in our sample, we detect emission fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 37 publications
3
81
0
Order By: Relevance
“…The L dwarf was reported as an active radio source by Antonova et al (2008), who estimated magnetic field strengths of ∼1.7 kG based on the detection of a single highly polarized burst of emission. The dominant emission was quiescent, the nature of which is still debated.…”
Section: Propertiesmentioning
confidence: 99%
“…The L dwarf was reported as an active radio source by Antonova et al (2008), who estimated magnetic field strengths of ∼1.7 kG based on the detection of a single highly polarized burst of emission. The dominant emission was quiescent, the nature of which is still debated.…”
Section: Propertiesmentioning
confidence: 99%
“…Recently, we have detected periodic pulses of 100% circularly polarized radio emission from four ultracool dwarfs Antonova et al 2008), with the periodicity for three of these dwarfs confirmed to correspond to the rotation period of the dwarf Hallinan et al 2008). Due to the high degree of polarization, the emission process for these pulses must be coherent.…”
Section: Introductionmentioning
confidence: 96%
“…Berger et al (2001) [4] reported the first detection of quiescent and flaring radio emission from the brown dwarf LP944-20, with anomalous quiescent radio luminosity larger than predicted from an empirical relation between the X-ray and radio luminosities of active stars with spectral types from F to M [6] by at least four orders of magnitude. Up to now, about 11 radio active ultracool dwarfs, with spectral type from M8 to L3.5, including a binary system, have been found from various survey [1,3,7,8]. Three of these have been shown to have periodic radio emission [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Pritchett (1984) [11] pointed out that a shell instability (or an incomplete shell instability) caused by a magnetic-field-aligned electric field would generate intense cyclotron emissions, in which a ring shell distribution, i.e., model, the initial electron-distribution function would be deformed by the presence of a magnetic-fieldaligned electric field which may accelerate the down-going electrons to a relativistic state and the mirror effect of the magnetic field which may increase the pitch angle of the electrons, so that an incomplete ring-shell distribution namely the so-called horseshoe distribution would be formed. We are developing a theoretical model to simulate the ECM instability and apply this model to map the emitting-region on ultracool dwarfs 1 . In this paper, we describe the method and preliminary results.…”
Section: Introductionmentioning
confidence: 99%